Evaluating The Implications of Indonesia's Omnibus Law: Legal, Political, and Economic Perspectives - Prasetyo, Vincentius Pantjahjono Heru; Bagastianto, Rian Cahyo; Widayanto, Anjas; Sulistyani, Oktavia Patma; Yanto, Heru Tri; Masruroh, Ainul (Universitas Islam Sultan Agung, 2025)
The Omnibus Law in Indonesia, enacted as Law No. 6 of 2023, has generated significant debate regarding its legal, political, and economic implications. The law seeks to simplify complex regulations and promote investment by overhauling approximately 80 existing laws across various sectors. Its primary aim is to foster economic growth, ease business processes, and create job opportunities. However, the law has been met with strong opposition from various stakeholders, including academics, labor unions, and NGOs, who argue that it disproportionately benefits corporations and foreign investors while undermining labor rights and environmental protections. This research aims to analyze the legal, political, and economic implications of the Omnibus Law, evaluating its effectiveness in achieving its intended goals while assessing its impact on labor rights and democratic governance. The study employs a normative legal research methodology, focusing on doctrinal analysis of the law’s provisions, consistency with constitutional principles, and alignment with democratic values. The findings reveal that while the law has the potential to stimulate economic growth, its legal ambiguities and bureaucratic inefficiencies pose challenges to effective implementation. Furthermore, concerns about transparency in the legislative process and the potential exacerbation of social inequality underscore the need for further refinement. The study concludes that the law must be adjusted to better align with Indonesia’s constitutional principles and social justice ideals.